Perancangan Aplikasi Kompresi File Audio dengan Algoritma Aritmetic Coding - Nurasyiah (JUKI : Jurnal Komputer dan Informatika, 2021)
Information exchange nowadays requires speed in sending information. The speed of this transmission depends on the size of the information. One solution to the above problem is compression. There are lots of data compression methods available today, but in this thesis we will discuss the working principles of the Arithmetic Coding algorithm with an implementation using Visual Basic 6.0. This algorithm performance analysis aims to determine the performance of this algorithm in * .MP3 and * .WAV audio files. In this system there are compression and decompression stages. The compression stage aims to compress the audio file size, while the decompression stage aims to restore the audio file size to its original size.